Eating Disorders and Obesity: The Challenge for Our Times - Hay, Phillipa; Mitchison, Deborah (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Eating Disorders have traditionally been considered apart from public health concerns about increasing obesity. It is evident that these problems are, however, related in important ways. Comorbid obesity and eating disorder is increasing at a faster rate than either obesity or eating disorders alone and one in five people with obesity also presents with an Eating Disorder, commonly but not limited to Binge Eating Disorder. New disorders have emerged such as normal weight or Atypical Anorexia Nervosa. However research and practice too often occurs in parallel with a failure to understand the weight disorder spectrum and consequences of co-morbidity that then contributes to poorer outcomes for people living with a larger size and an Eating Disorder. Urgently needed are trials that will inform more effective assessment, treatment and care where body size and eating disorder symptoms are both key to the research question.
English
Keywords: dietary patterns; family functioning; binge-eating disorder; eating disorders; eating disorders-related symptoms; mothers; Bulimia Nervosa; children; menstrual dysfunction; young children; prevention; usability study; bulimia nervosa; adolescents; brain activity; para athlete; women; treatment; exercise; students; nutrient deficiency; feeding practices; food industry; nurse; loss of control eating; body satisfaction; frequency bands; BMI; biofeedback; BED; orthorexia nervosa; binge eating disorder; eating behavior; psychometric; EEG-Neurofeedback; NMUR2; school setting; addictive-like eating; executive function; health education; engagement; low energy availability; binge eating; dieting; bone mineral density; eating behaviour; energy availability; obesity; visceral adipose tissue; binge-type eating; International Classification of Diseases; athlete; EEG; weight loss; obesity risk; weight; nucleus accumbens; fMRI-Neurofeedback; food addiction; nutrition